Unveiling genetic richness: Profiling broad bean diversity in the Nilgiri Hills through morphological, biochemical, and SSR markers - Ajay, A R; Karthikeyan, S; Geethanjali , S; Raja, P; Thamaraiselvi, S P (Plant Science Today, 2025)
This study aimed to uncover the genetic relationship among broad bean genotypes to establish a high-yielding strain to elevate the status of this underutilized vegetable in the country. Twenty broad bean genotypes were assessed using randomized block design to reveal their genetic connections derived from twelve morphological factors and seven biochemical attributes. In addition, SSR primers were used to examine the molecular differences. The multifaceted data obtained were combined to evaluate genetic distinctions among these genotypes. The genetic analysis revealed that pod production per plant exhibited superior values of both phenotypic and genotypic coefficient of variation. Association analysis of green pod yield featured a strong positive correlation with seed yield, carbohydrate content, pod count per plant and 100 seed mass. The most notable positive direct influence on green pod yield was due to 100 seed weight. Choosing traits with a strong correlation with pod yield, along with moderate to high levels of phenotypic coefficient of variation (PCV), genotypic coefficient of variance (GCV), heritability and genetic progress would boost the effectiveness of the broad bean improvement program. The cluster analysis sorted the 20 genotypes into six groups, highlighting the considerable variation within each group. Among the SSR primers screened, the peak PIC score of 0.660 was noticed for the primer GBSSR-VF-172. The dendrogram constructed based on SSR markers resulted in two major clusters, illustrating the genetic affiliations and diversity within the genetic lines. This multidimensional characterization highlighted significant genetic disparities among broad bean genotypes, facilitating the selection of superior genotypes to develop high-yielding cultivars.